STUDI FENOLOGI DAN PENENTUAN MASAK FISIOLOGIS BENIH PURWOCENG - Rusmin, Devi; Darwati, Ireng (JURNAL AGRONIDA, 2018)
The experiment was conducted at Gunung Putri Experimental Station and PlantPhysiology Laboratory of Indonesian Medicinal and Aromatic Crops Research Institute(IMACRI), from November 2008 to July 2009. The aim of the experiment was to determinephysiological maturity of Pimpinella pruatjan seed and to study its morphological structures.Observation and sampling using one hundred plants with four replications. Results of theexperiment showed that the physiological seed maturity on the first and third umbell of P.Pruatjan was achieved at 7 weeks after anthesis, and physiological seed maturity on thesecond umbell was achieved at 8 weeks after anthesis. Seed dry weight on the physiologicalseed maturity on first, second and third umbells were 166,87; 158,20, and 141,35 mg/100pericarp, respectively. Germination percentage and germination speed on the first, secondand third umbells were 5,75 % and 0,22 %/etmal; 22,75 % and 0,94 %/etmal; 10,50 % and0,38 %/etmal, respectively.Keywords: flowering, pruatjan, seed quality, morphology